Determination of Stress Levels among Post Graduate Students of Gandhi Medical College, Bhopal: A Cross- Sectional Study - Nisha Singh; Mayan Badkur; Yogendra Chouhan; Seema Patel; Amreen Khan; Veena Melwani (Medsci Publications, 2018)
Background: Medical education is highly challenging and often places heavy demands on mental resources of its students, stretch- ing their psychological distress and making them vulnerable to high levels of negative affective states. The present study was un- dertaken to determine the degree of stress prevalent among the Post Graduate students of Gandhi Medical College Bhopal &to identify probable factors responsible for it. Materials and Methods: A prospective, cross-sectional survey was carried out amongst 75 post graduate students. Convenient sam- pling method was used. Semi-structured questionnaire, prepared using Stress Indicator Questionnaire was used for assessment. Result: A total of 75 Post graduate students were included in the study, of which 36 (48%) were males and 39 (52%) were females. Maximum respondents, 59 (78.67%) were of ≤30 years of age. 76% were from clinical branches and 53.33% were first year residents. Physical and emotional factors were found to be responsible for highest levels of stress among the post graduate students. Conclusion: Participants from clinical branches showed higher degree of physical stress as compared to those from non clinical. Male subjects had a higher degree of emotional stress as compared to the female subjects. Post graduates had poor knowledge and ac- cess regarding stress busting measures.